Efeitos da remoção da tilápia do Nilo, Oreochromis niloticus (Linnaeus, 1758), na estrutura trófica da ictiofauna em um reservatório do semiárido brasileiro - Moura, Cristiane de Carvalho Ferreira Lima (Universidade Federal Rural do Semi-Árido, 2014)
This study aimed to analyze the influence of the exotic species Oreochromis niloticus, before and after its removal in the fish assemblage, characterizing its trophic guilds over the months in a reservoir of the Brazilian semiarid. Data were sampled in two periods, before removal of exotic species (May 2012 to January 2013) and after removal (April 2013 to November 2013). Six species were analyzed (Oreochromis niloticus, Prochilodus brevis, Hypostomus cf. paparie, Hoplias gr. Malabaricus, Astyanax bimaculatus and Leporinus piau) whose values of the Feeding Index (IAi) were used. The Morisita-Horn similarity coefficient was used to assess the feed similarity between species and establish four trophic categories (insectivorous, omnivorous, detritophagous / iliófaga and piscivorous). To assess the possible variations due to the presence of the species O. niloticus, we used the Feeding Index of species in Bray-Curtis similarity matrix, using the ordination analysis (NMDS) that detects if there was difference in items consumed by the species. The result of Multivariate Analysis Canonical Correlation (CCA) between abiotic factors (rainfall, pH, turbidity, dissolved oxygen) and biotic factors showed that the diet is associated with abiotic factors with little correlation with the presence of scavenging / iliófagas species. The species continued inserted in the same categories, in both periods analyzed, and therefore the number of guilds did not change. It is possible that the species O. niloticus had no time to settle in the environment during the study period, it is therefore necessary a long-term study to verify the relationship between abiotic factors and the establishment of tilapia in protected areas
Effects of removal of Nile tilapia, Oreochromis niloticus (Linnaeus, 1758) in the trophic structure of the ichthyofauna in a Brazilian semiarid reservoir
Keywords: Fish; Nile tilapia; Trophic guilds; Fishes; Semiarid; Pescados; Tilápia do Nilo; Guildas tróficas; Peixes; Semiárido; CIENCIAS BIOLOGICAS::ECOLOGIA